Respuesta :
Answer:
A.
Explanation:
Just plug in the points to each equation.
A. x + 2y = 2
Plugging in (-6,4) (-6) + 2(4) = 2 ---> -6 + 8 = 2
Plugging in (2,0) (2) + 2(0) = 2 ---> 2 + 0 = 2
B. 2x + y = -16
Plugging in (-6.4) 2(-6) + (4) = -16 ---> -12 + 4 = -16 --> -8 [tex]\neq -16[/tex]
Because the first point didn't work there is no need to check the second one.
C. x + 2y = -8
Plugging in (-6,4) (-6) + 2(4) = -8 ---> -6 + 8 = -8 --> 2[tex]\neq -8[/tex]
Again, because the first point didn't work there is no need to chek the next.
D. 2x + y = 4
Plugging in (-6,4) 2(-6) + (4) = 4 ---> -12 + 4 = 4 --> -8[tex]\neq 4[/tex]
Even though the answer was A. you should still check each on of them because there can always be a mistake in your work.
Answer:
A
Step-by-step explanation:
To find the equation of a line, the first thing that must be determined is the lines gradient. This can be determined by using the formula:
m = (Δy) / (Δx)
m = (4-0) / (-6-2)
m = 4 / -8
m = -0.5
The gradient has been determined, now we determine the y-intercept by using a point it passes through (either point cant be used because the line will pass through bother coordinates given)
y = mx + c (Using the point (2,0))
0 = (-0.5)(2) + c
c = 1
Since we have the y-intercept, a formula can be created for the line, and rearranging it, we can then find the correct option.
y = mx + c
y = (-0.5)x + 1
2y = -x + 2
x + 2y = 2